Imaging Behavior of the Normal Adrenal on Ferumoxytol-Enhanced MRI: Preliminary Findings - Gunn, Andrew J.; Seethamraju, Ravi T.; Hedgire, Sandeep; Elmi, Azadeh; Daniels, Gilbert H.; Harisinghani, Mukesh G. (American journal of roentgenology (1976), 2013)
Ultrasmall superparamagnetic iron oxide nanoparticles, such as ferumoxytol, produce decreased MR signal on susceptibility-inducing T2*-weighted sequences in tissues of the reticuloendothelial system. However, acute iron deposition in the adrenals has not been reported. The purpose of this article is to report our initial observations of the imaging behavior of the normal adrenals on ferumoxytol-enhanced T2*-weighted magnetic resonance imaging. Quantitative T2* imaging was performed at 3 T using a breath-hold monopolar multiecho gradient echo sequence with six equally spaced in-phase echoes in nine patients. Changes in signal-to-noise ratio (SNR) were analyzed prior to and 48 hours after ferumoxytol administration in the adrenals, liver and spleen (positive controls), and pancreas and skeletal muscle (negative controls). In comparison with unenhanced images, there was an average SNR decrease of 67.4% in the right adrenal, 77.6% in the left adrenal, 68.4% in the liver, 89.1% in the spleen, 15.0% in the pancreas, and 9.5% in skeletal muscle on T2*-weighted images obtained 48 hours after ferumoxytol administration. The decrease in SNR observed in the adrenals was significantly greater than that seen in the pancreas and skeletal muscle (left adrenal, p < 0.0001; right adrenal, p = 0.0002) and similar to that seen in the liver and spleen. The normal adrenal loses signal on ferumoxytol-enhanced T2*-weighted MRI. Acute iron deposition within the adrenals has not been previously described. The mechanism of ferumoxytol uptake in the adrenal and potential clinical applications warrant further investigation.